Pengembangan Sistem Pemesanan Paket Wisata berbasis Website menggunakan Midtrans Webservice sebagai Payment Gateway (Studi Kasus: Majapahit Tour & Travel) - Hendro Dwi Prasetyo; Muhammad Aminul Akbar; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Majapahit tour & travel is a tour package provider service located in Mojokerto. Majapahit tour & travel business process is carried out by online and offline methods. Booking via online via whatsapp, Instagram and telephone, while offline bookings can directly come to the Majapahit tour & travel office, from these two ways there are obstacles, namely customers must still come to the office to provide proof of the seriousness of ordering tour packages. Another obstacle is that conventional tour package payments have not met the needs of the public for technological developments that are starting to take advantage of digital payments. Based on these problems, the creation of a website and payment system using online payment can be used as a solution to problems in Majapahit tour & travel, so that customers do not have to come to the office to order packages and payments can be made online with the midtrans payment gateway integrated with the application. This system was developed using the SDLC (Software Development Life Cycle) method, namely Waterfall and payments using midtrans payment gateways. Then the programming language uses PHP with the Laravel framework. System development starts from needs analysis, design, implementation to the testing stage. After being designed and implemented, blackbox testing was found out that from 18 functional needs, it produced valid results according to the needs analysis, then compatibility testing was produced from 8 types of browsers that were tested, good results were produced on all types of browsers, and usability testing produced an average value of 80 which was included in the good category, with a grade scale of B and included acceptable